Sikap terhadap vaksin Covid-19: Perbedaannya menurut faktor demografis, kesehatan, dan ekonomi serta pengaruhnya pada intensi vaksinasi - Aning Az Zahra; Aftina Nurul Husna (Jurnal Psikologi Sosial, 2023)
One way to deal with the COVID-19 outbreak is by vaccination of COVID-19. On the other hand, there are still some attitude responses to the vaccine, There are acceptance, hesitance, and resistance. This study aims to (1) determine the differences in attitudes towards the Covid-19 vaccine in terms of demographic factors, health factors, and economic factors. (2) find out whether attitudes towards the Covid-19 vaccine affect the intention (willingness) to be vaccinated. The method in this study uses quantitative methods using descriptive statistical analysis. Testing the hypothesis that there are differences in attitudes towards the Covid-19 vaccine according to demographic factors, health status, and personal economic conditions using ANOVA while testing the effect of attitudes towards the Covid-19 vaccine on vaccination intentions using Ordinal Logistic Regression Analysis. The results of this study were attitudes towards Covid-19 vaccination (SVC) based on different demographic factors based on age (F = 2.98, p < 0.05). Age >45 years and over represents more doubt. The difference between SVC and health status was very significant in terms of having been infected or not (F=7.246, p<0.01).